A Consensus to Revise the Minimum Speech Test Battery--Version 3. - Dunn, Camille C.; Zwolan, Teresa A.; Balkany, Thomas J.; Strader, Heather L.; Biever, Allison; Gifford, René H.; Hall, Melissa W.; Holcomb, Meredith A.; Hill, Heidi; King, English R.; Larky, Jannine; Presley, Regina; et al. (American Journal of Audiology, 2024)
Purpose: The Minimum Speech Test Battery (MSTB) for adults was introduced in 1996 (Nilsson et al., 1996) and subsequently updated in 2011 (Advanced-Bionics et al., 2011). The MSTB has been widely used by clinicians as a guide for cochlear implant (CI) candidacy evaluations and to document post-operative speech recognition performance. Due to changes in candidacy over the past 10 years, a revision to the MSTB was needed. Method: In 2022, the Institute for Cochlear Implant Training (ICIT) recruited a panel of expert CI audiologists to update and revise the MSTB. This panel utilized a modified Delphi consensus process to revise the test battery and to improve its applicability considering recent changes in CI care. Results: This resulted in the MTSB--Version 3 (MSTB-3), which includes test protocols for identifying not only traditional CI candidates but also possible candidates for electric--acoustic stimulation and patients with single-sided deafness and asymmetric hearing loss. The MSTB-3 provides information that supplements the earlier versions of the MSTB, such as recommendations of when to refer patients for a CI, recommended patient-reported outcome measures, considerations regarding the use of cognitive screeners, and sample report templates for clinical documentation of pre- and post-operative care. Electronic versions of test stimuli, along with all the materials described above, will be available to clinicians via the ICIT website (https://www.cochlearimplanttraining.com). Conclusion: The goal of the MSTB-3 is to be an evidence-based test battery that will facilitate a streamlined standard of care for adult CI candidates and recipients that will be widely used by CI clinicians.